Candidate experience in recruitment cycle facilitating employer brand: a case study of Idea Cellular Limited in the Delhi and NCR circle. (2019) - Gupta, Jaya; Mohan, Dhyanendra
The telecom industry in India has been growing at an accelerated pace. Acquiring the right talent and creating a positive brand pull is becoming very important. It is important for HR to focus upon meeting the candidate experience across all stages of recruitment cycle as a catalyst to boost its employer brand. A detailed analysis of the recruitment process was conducted in the course of filling two positions in the finance and accounts department of Idea Cellular Infrastructure Services Limited. It was observed that several minor issues needed to be addressed that could significantly boost the candidate experience. The present case captures key candidate touch points which are crucial to improve the overall experience. The case study seeks insight on some changes that need to be implemented that could help to improve the candidate experience in the endeavour to transform its brand image as the best place to work.